2022
DOI: 10.3390/ani12040490
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomic Changes in Dogs with Different Stages of Chronic Heart Failure

Abstract: MMVD, the most common cause of CHF in dogs, is a chronic disease with variable clinical signs, with some patients remaining asymptomatic while others develop CHF. Here, we aimed to evaluate serum proteins by proteomic analysis in dogs at different stages of CHF due to MMVD, and proteome behaviors after conventional treatment. A total of 32 dogs were divided equally into four groups—stage A (healthy/controls), stage B2 (asymptomatic), stage C and stage D (symptomatic)—according to the ACVIM consensus. Serum pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…In our study, down-regulation of PON1 ( Fig. 4 ) could be a marker of disease progression to severe symptoms as it was reported that the presence of inflammation and oxidative stress is associated with a decrease of serum PON1 in cardiovascular diseases [ 51 ]. Furthermore, a low level of PON1 may exacerbate the innate proinflammatory reaction to virus infection as it was demonstrated that PON1 suppresses macrophage overreaction and sustains inflammation in atherosclerosis [ 52 ].…”
Section: Discussionmentioning
confidence: 56%
“…In our study, down-regulation of PON1 ( Fig. 4 ) could be a marker of disease progression to severe symptoms as it was reported that the presence of inflammation and oxidative stress is associated with a decrease of serum PON1 in cardiovascular diseases [ 51 ]. Furthermore, a low level of PON1 may exacerbate the innate proinflammatory reaction to virus infection as it was demonstrated that PON1 suppresses macrophage overreaction and sustains inflammation in atherosclerosis [ 52 ].…”
Section: Discussionmentioning
confidence: 56%
“…To date, several studies have provided a deeper insight into the changes in serum proteomes of dogs affected by MMVD [ 8 , 9 , 10 , 11 ]. All these studies were performed on naturally occurring MMVD, and, so far, only one study has compared the serum profiles of consecutive MMVD stages (B2, C, and D) in comparison to stage A (healthy dogs genetically predisposed to developing MMVD) [ 11 ]. To the best of our knowledge, there is no study that has compared the proteomic profiles of asymptomatic B1 and B2 stages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all these proteins were also enriched in hemostasis, and several in fibrin clot formation ( Table 2 ). Differences in serum tetranectin (CLEC3B) levels have previously been found in canine MMVD [ 9 , 11 ]. Due to stimulating activity on extracellular proteolysis in collagen-, fibrin-, and plasminogen-containing tissues, CLEC3B seems to play a significant role in tissue remodeling, potentially by inducing plasminogen activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic and peptidomic analysis allow evaluation of changes in protein and peptide compositions, and previous study on serum proteomics in dogs with MMVD has shown that dogs with different stages of CHF showed different serum protein compositions ( 4 ). Similarly, Petchdee et al investigated serum peptidomics in dogs with MMVD, which demonstrated the presence of peptides including mitogen-activated protein kinase, kallikrein, and tenascin-C in the group with progressed MMVD.…”
mentioning
confidence: 99%